Equine Podotrochlear Apparatus - Histologic Characterization - De Bastiani, Grasiela; De La Côrte, Flávio Desessards; Ramos, Adriano Tony; Jacobsen, Tainã Kuwer; Kommers, Glaucia Denise; Martinez-Pereira, Malcon Andrei (Acta Scientiae Veterinariae, 2022)
Background: The navicular syndrome may be associated with alterations in other podotrochlear apparatus components, such as the deep digital flexor tendon, collareral sesamoid and distal sesamoid ligaments, podotrochlear bursa and distal sesamoid bone. However, the clinical significance and nature of these changes are not well understood, many of descriptive reports about distal sesamoid bone lesions are rarely accompanied by a complete and comprehensive comparison with animals of the control group. The aim of this study was to described histologically findings of the podrotrochlear apparatus components, allowing the understanding of the inserts and their microscopic appearance, thus providing the future recognize of their alterations. Materials, Methods & Results: Fourteen samples of the podotrochlear apparatus were taken out of 44 equine thoracic limbs specimens, separated at the radiocarpal joint of Crioulo and Thoroughbred horses, with an average age of 6.0-year-old, coming from a private clinic in southern Brazil. The thoracic limbs specimens were refrigerated at 4ºC at the clinic and then they were sent to the University Federal of Santa Maria (UFSM). Once at the University laboratory, the specimens were dissected to isolate the podotrochlear apparatus from each one. Subsequently, transversal and longitudinal samples from the distal sesamoid bone, deep digital flexor tendo, distal sesamoid ligament, colateral sesamoid ligament, were collected and podotrochlear bursa which were processed at the Veterinary Pathology Laboratory of the UFSM and University Federal of Santa Catarina (UFSC). The tissues samples were fixed in a 10% formaldehyde solution for 14 days and routinely processed for histology. The samples were sectioned at 3 µm and stained using the hematoxylin-eosin (H-E) routine method. The bone samples, after fixation, underwent a decalcified process in a formic acid-sodium citrate aqueous solution and routinely processed for histopathology. Histologic tendons evaluation showed that it is arranged in honeycombs fascicles in a transverse section observation. The tendinous fibers have a more compact and aligned collagen fibers arrangement due to the dense connective tissue. The synovial membrane of the podotrochlear bursa is composed of a cubic pseudo conjunctival epithelium arranged with a layer of synoviocytes forming villi towards the lumen. This characterization is very similar to that of the synovial joint membrane. The collateral sesamoid ligament fibers are not perfectly aligned, occurring at their confluence in some areas accompanied by the dissection of adipose tissue. The distal sesamoide ligament fibers, composed by of loose connective tissue associated with synoviocytes and vascular stroma. The articular surface of the distal sesamoid bone is arranged in 3 layers of chondrocytes embedded in a hyaline matrix. There was a clear differentiation between the subchondral bone area and the fibrocartilage tissue in the palmar aspect of the distal sesamoid bone. Discussion: The morphophysiological characterization of the podotrochlear structures inside the hoof capsule it is important for the future recognition of abnormalities and the possible hypothesis that originates the podotrochlear syndrome. These changes have great clinical relevance and very often associated of distal limb lameness in horses. The normal macroscopic, ultrasonographic and radiographic images along with the histomorphometric study of the podotrochlear structures have contributed for the morphophysiological comprehension and consequently future interpretation of the podotrochlear structures diseases. Keywords: podotrochlear apparatus, distal sesamoide bone, deep digital flexor tendon, navicular syndrome, histological findings.